Proteolysis of PDO Serpa cheese made with Cynara Cardunculus L ecotypes during ripening - Pinheiro, C. (2019)
Portugal and Spain have a strong tradition of cheesemaking from raw ewe’s cheese made with the aqueous extracts of Cynara cardunculus L. dried flowers. Serpa cheese is an example of a Portuguese regional cheese with the label of Protected Designation of Origin (PDO), that is characterized with a semi-soft texture and an exquisite flavor. The renewed interest in the enzymes of the Cynara cardunculus L. coagulant prompted to the aim of this work that was to evaluate the effect of Cynara cardunculus L. three ecotypes on Serpa cheese proteolysis. Therefore, cheese samples were analysed by urea-PAGE, and nitrogen fractions (total nitrogen, water soluble nitrogen and non-protein nitrogen) and three ecotypes were used (Cynara 1, Cynara 2, Cynara 3) and compared with a commercial animal rennet (Animal) after 0, 2 and 5 weeks of ripening. It was possible to stablish the pattern of the casein fractions degradation and, at the end of ripening (5weeks), results showed that no significant differences were found in cheeses made with the three ecotypes, and they showed a higher degradation of αS-caseins (47,42%) then β-caseins (24,27%). However, differences were found between cheeses made with the vegetable coagulant and those made with animal coagulant, especially regarding β-caseins results. Observing the nitrogen fractions, all samples obtained with vegetable coagulant presented a higher degree of proteolysis than the samples coagulated with rennet, being Cynara 1 the coagulant that presented higher proteolytic power